Prisoners [videorecording (Blu-Ray)] - Guzikowski, Aaron; Jackman, Hugh; Gyllenhaal, Jake, 1980-; Davis, Viola, 1965-; Bello, Maria, 1967-; Howard, Terrence; Leo, Melissa; Dano, Paul, 1984- (Warner Bros. Entertainment, 2013)
Keller Dover is facing every parent's worst nightmare. His six-year-old daughter, Anna, is missing, together with her young friend, Joy. The only lead is a dilapidated RV that had been parked on their street. Heading the investigation, Detective Loki arrests its driver but a lack of evidence forces his release. As the police pursue multiple leads, Dover knows his child's life is at stake and decides he must take matters into his own hands. How far will he go to protect his family?